Probabilistic Determination of Groundwater Using Semi-Qualitative MCDA-Based Analytic Hierarchy Process Approach in Sunsari District, Nepal - Linkha, Tika Ram; Khatiwada, Shambhu Prasad; Lama, Furbe; Rai, Dil Kumar (The Third Pole: Journal of Geography Education, 2022)
Groundwater served as the major source of water for existing biophysical species in an ecosystem. In recent years, depletion of the level of groundwater becomes an emerging serious environmental issue due to the anti-reciprocal man and human activities such as global climate change. This study aims to examine the groundwater potential areas using the semi-qualitative research design, based on Analytic Hierarchy Process. The focused is based on the Geographic Information System for the analysis of determining factors, such as distance from the stream and river, precipitation, pond frequency, normalized difference water index, land-use/land cover, drainage density, slope gradient, soil, and topographic wetness index. The Receiver Operating Characteristics were used to check the accuracy of the final calculated map of the groundwater potential zone. The 5 points Likert scale ranges very poor (1) to very high (5) used to analyse the groundwater potential zones. The result shows that 0.81 percent area is very poor for the potentiality of groundwater in the study area. Other scale contained 8.13 for poor, moderate (19.94%), high (39.72%) and very high potential zones (31.41%). The Receiver Operating Characteristics result showed that under the curve success rate is 0.64% and the prediction rate is 0.76%. This result shows a reliable degree of predictability of groundwater near the spatial distribution of marshes, lakes, and water bodies in the study area. The finding shows that the very high potentiality of groundwater areas are determining by the factors of precipitation, pond frequency, distance from river and stream, drainage density, land-use/land cover, soil, and slope in the study area. The result of this empirical analysis can be applied to analyze sustainable and effective water resources management activities.